Optimizing 5-aza-2′-deoxycytidine treatment to enhance the development of porcine cloned embryos by inhibiting apoptosis and improving DNA methylation reprogramming. (October 2020) - Qu, Jiadan; Wang, Xiangyu; Jiang, Yujia; Lv, Xiaofei; Song, Xuexiong; He, Hongbin; Huan, Yanjun
Abstract: Apoptosis and incomplete DNA methylation reprogramming in cloned embryos reduce cloning efficiency. 5-aza-2′-deoxycytidine (5-aza-dC) is proven to regulate apoptosis and DNA methylation reprogramming, however, the treatment method and potential role of 5-aza-dC during cloned embryo development are still not well studied. This study displayed that treating donor cells with 5-aza-dC (AN group) significantly reduced the blastocyst rate, while treating cloned embryos (NA group) or both donor cells and cloned embryos (ANA group) significantly promoted the blastocyst formation, and the ANA group was the best treatment of 5-aza-dC to enhance the development of cloned embryos. Then, compared with the NT group, the ANA group showed the significantly enhanced nuclear remodeling. The apoptotic cell numbers and rates of blastocysts were significantly reduced, and the expression levels of significantly upregulated anti-apoptosis gene Bcl2l1 and downregulated pro-apoptosis genes Bax, P53 and Caspase3 were observed in the ANA group. Further study demonstrated that the transcription levels of DNA methylation reprogramming genes Dnmt1, Dnmt3a, Tet1 and Tet3 were significantly upregulated, and, significant genomic DNA remethylation, DNA demethylation of pluripotency gene Oct4, and DNA remethylation of tissue specific gene Thy1 were observed at the blastocyst stage in the ANA group. Embryo development related genes including Igf2, H19, Oct4, Nanog, Sox2, Eif1a, Cdx2 and ATP1b1 were significantly upregulated, and Thy1 and Col5a2 were remarkably silenced at the 4-cell and blastocyst stages in the ANA group. In conclusion, the best 5-aza-dC treatment enhanced the development of cloned embryos by inhibiting apoptosis and improving DNA methylation reprogramming. Highlights: A full investigation of 5-aza-dC treatment on the development of cloned embryos. Treating both donor cells and embryos is best for 5-aza-dC in cloned embryos. Enhanced embryo nuclear remodeling after this suitable treatment. Apoptosis is significantly reduced after this appropriate treatment. Improved DNA methylation and gene expression after this best design.